Analysis of impact strength and hardness of waste HDPE composites reinforced with ijuk fiber - Nurfahmi, Ilyas; Rahmat Doni Widodo; Muhammad Irfan Nuryanta (JTTM : Jurnal Terapan Teknik Mesin, 2026)
The utilization of HDPE waste as a composite material is increasingly developing due to the industry's demand for materials that are lightweight, economical, and environmentally friendly. The properties of ijuk fiber, which has high strength and good elasticity modulus, make HDPE polymers stronger when used to be transformed into composite materials. The aim of this study is to analyze the effect of variations in the mass fraction of ijuk fiber on the mechanical properties of HDPE-based composites through impact and hardness tests. The composite material was made using HDPE plastic bottle caps as the matrix and alkalized ijuk fiber as reinforcement, with fiber mass fraction variations of 0%, 10%, 15%, and 20%. Specimens were made using an oven at 150°C, followed by hydraulic hot pressing at a pressure of 90 tons. Mechanical characterization was conducted using Charpy impact testing (ASTM D6110) and Shore D hardness testing. The research results show a consistent increase in mechanical properties with the increasing fraction of fibers used. The highest impact test result of 0.285 kJ/m² was obtained at a 20% fiber content, and the highest hardness test result of 60.89 Shore D was obtained at a 20% fiber content. These results indicate that the addition of ijuk fibers improves the energy absorption value and surface resistance of HDPE composite materials. Therefore, adding fibers up to 20% effectively enhances the mechanical performance of HDPE composites reinforced with ijuk fibers